The Analysis of Purposes of Science Teacher Candidates in Using Social Media - (:unkn) unknown (ANI YAYINCILIK, 2013)
Problem Statement: With the Internet becoming an inseperable part of our lives, the role of social media in daily life is rapidly increasing with each passing day. In this respect, it is important to identify the purposes of teacher candidates in using social media tools that rapidly improve and become widespread in teacher training institutions. Purpose of the Study: In this study, it is intended to identify the variables by which the purposes of science teacher candidates in using social media vary and their opinions about the use of social media in education. Methodology: For this purpose, a scale on the use of social media by teacher candidates has been applied to a sample group of 255 people. The data was evaluated quantitatively with SPSS 17.00 software. In order to identify the views of science teacher candidates on the use of social media in education, five open-ended questions were asked to five people who were randomly selected from the sample group. Findings and interpretation: The research results show that the purposes of science teacher candidates in using social media vary according to demographic characteristics (sex, grade level, family income) and to variables related to Internet usage (frequency of Internet usage, the time spent on the Internet, blog ownership, the purpose of using the Internet, the frequently used social media tools). It is found that science teaching students generally have a positive attitude towards the use of social media in education. Conclusion and Discussion: It is possible to create educational settings for scientific discussions and for sharing ideas on social media. With the use of these settings in education, a lot of activities that will be time-consuming in the class environment can be carried out on social media and science teaching students can be offered many opportunities and tools such as enjoyable homework assignments, complementary videos etc. For example, after the lesson on the subject of cell is completed in the class environment, a video about the structures forming the cell can be shared with the group on the Facebook and a related discussion can be initiated between students where the teacher can also contribute with comments. Or the followers of the teacher can share the stages of an experiment on Twitter and everybody can contribute to the design of a new experiment.
Keywords: Social media; Education; Science Teacher Candidates; Science education